2022
DOI: 10.1111/dth.15543
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic acid – A novel topical agent in reducing signs of photoaging

Abstract: Continuous production of reactive oxygen species, induced by UV radiation, is one of the main mechanisms contributing to skin photoaging. Therefore, the use of novel superior antioxidants, which ferulic acid belongs to, is an innovative treatment option. The aim of this study was to evaluate the effect of 14% ferulic acid peel on skin hydration, topography, the level of melanin, and the severity of erythema, in people with skin photoaging symptoms. Twenty women aged 45–60, received eight treatments of chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…It efficiently alleviates the negative effects of UVinduced oxidative stress [93,94]. In vivo studies have confirmed ferulic acid skin firming, moisturizing, and pigmentation regulating activity [95].…”
Section: Discussionmentioning
confidence: 87%
“…It efficiently alleviates the negative effects of UVinduced oxidative stress [93,94]. In vivo studies have confirmed ferulic acid skin firming, moisturizing, and pigmentation regulating activity [95].…”
Section: Discussionmentioning
confidence: 87%
“… 16 , 17 FA supplementation can effectively delay immunosenescence. Therefore, it is widely used as an antiphotoaging agent in skin, 18 , 19 but its molecular mechanism remains unclear. Abundances of PS, a lipid metabolite, increased significantly in habitual coffee consumers.…”
Section: Resultsmentioning
confidence: 99%
“…While α-tocopherol (free vitamin E) is renowned for stabilizing the lamellar lipid layers in the SC (Thiele, 2001), other antioxidants like vitamin C have also demonstrated clinical improvements in aging skin when applied topically (Thiele and Ekanayake-Mudiyanselage, 2007). Moreover, the advancements in skin care have introduced a variety of other topical antioxidants, such as ferulic acid, resveratrol, and niacinamide (Baxter, 2008;Boo, 2021;Zduńska-Pęciak et al, 2022), which, when used individually or synergistically, offer a robust defense against oxidative stress and enhance the skin's resilience against environmental aggressors like UV radiation (Baxter, 2008;Farris et al, 2014;Hahn et al, 2016;Rattanawiwatpong et al, 2020;Boo, 2021;Zduńska-Pęciak et al, 2022).…”
Section: Antioxidant and Uv Protectionmentioning
confidence: 99%